PENGARUH KUALITAS PRODUK, PELAYANAN DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - Afiatin (Education : Jurnal Sosial Humaniora dan Pendidikan, 2021)
This study aims to determine the influence of Product quality. Service quality and Customer trust on Customer loyalty. Where is the independent variable consist of Product quality variable. Service quality variable, and Customer trust variable influences Customer Loyalty variable as the dependent variable. This research was conducted at Enterprise in Surabaya. Methods of data collection in this study is questionnaires filled out by the respondents are consumers of Enterprise that have been bought the blank wedding invitation cards at least twice. Taking sample of 50 respondents in this study using a purposive sampling method.